Malondialdehyde precursors in gamma-irradiated DNA, deoxynucleotides and deoxynucleosides. - Janicek, M F (1985)
Gamma-irradiation of DNA, deoxynucleosides, or deoxynucleotides produces material that reacts with thiobarbituric acid to form a chromophore with maximum absorbance at 532 nm. This material is not malondialdehyde. We have identified a new radiation product (thymin-1'-yl)-propenal as the TBA-reactive product of gamma-irradiation of thymidine. Thymine-propenal has been described by other investigators as a product of bleomycin-treatment of DNA. Irradiation of thymidine nucleotides produces phosphorylated precursors to thymine-propenal. Studies of the requirements for formation of TBA-reactivity indicate a mechanism involving reaction of a free radical with the deoxyribose moiety and molecular oxygen. On the basis of these results it is proposed that gamma-irradiation produces TBA-reactive material in DNA by the same reaction sequence in which bleomycin catalyzes the formation of base-propenals in DNA. Bleomycin and gamma-irradiation differ in the extent to which the sequence proceeds to completion with release of free base-propenals.